2017
DOI: 10.1097/jom.0000000000000937
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Conditions Increase Preventable Crash Risks Among Truck Drivers in a Cohort Study

Abstract: Objective This study aims to quantify the crash risk for truck drivers with multiple comorbid medical conditions, after adjusting for confounders. Methods This retrospective cohort of 38,184 drivers evaluated concomitant medical conditions and subsequent crash data between 1/1/2005–10/31/2012. Hazard ratios (HRs) and 95% confidence intervals (95% CI) were calculated for any cause and preventable crashes of varying severity. Results Drivers with three or more medical conditions had significantly increased r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 40 publications
1
28
0
Order By: Relevance
“…Ulhôa et al reported that 0% of Brazilian participants asked used psychotropic drugs, 45 which is similar to findings from a US study. 12 However, Shattell et al found a relatively high prevalence of reported use of cannabis (3.4%), opioids (2.5%) and sedatives (1.8%) in the past month in a sample of US truck drivers. 2 Riva et al found a higher drug use in a sample of Italian truck drivers where 15.6% reported using recreational drugs, and of those, 12% reported they were addicted.…”
Section: Resultsmentioning
confidence: 97%
“…Ulhôa et al reported that 0% of Brazilian participants asked used psychotropic drugs, 45 which is similar to findings from a US study. 12 However, Shattell et al found a relatively high prevalence of reported use of cannabis (3.4%), opioids (2.5%) and sedatives (1.8%) in the past month in a sample of US truck drivers. 2 Riva et al found a higher drug use in a sample of Italian truck drivers where 15.6% reported using recreational drugs, and of those, 12% reported they were addicted.…”
Section: Resultsmentioning
confidence: 97%
“…A recent article it was found that CMV drivers with heart disease were more likely to have experienced a prior truck crash and drivers with multiple medical conditions were also more likely to have a crash . Changes in prevalence of medical conditions may indicate increased risk of crashes among this population.…”
Section: Discussionmentioning
confidence: 99%
“…In motor vehicle highway safety applications, these retrospective case-control studies are typically conducted using police crash reports. In the U.S., crash reports include information pertaining to number of vehicles, involvement of pedestrians, number of injuries/fatalities, road type, crash location, date-time, intersection type, presence of a nearby work zone, weather conditions, and road surface conditions [14,15]. While a lot of information can be captured in these reports, case-control studies are inherently limited for two main reasons.…”
Section: Background: Study Designsmentioning
confidence: 99%